‘Teach, reduce and discharge’: Community nurses’ textual production of ‘independence’ and the coordination of discharge from home care services (Journal of Comparative Social Work, 2016)
Over the past three decades, the Canadian healthcare system has undergone significant reform and restructuring. As a result, healthcare and healthcare costs are relocated from hospitals to the community (McGregor, 2001). Text-based technology is increasingly used to standardize care and contain healthcare spending. This paper examines an example of a text-based technology used in the School Health Support Services programme for students with diabetes in Ontario, Canada. Using institutional ethnography, the inquiry starts with parents’ concerns regarding the premature termination of nursing care for their children with diabetes at school. The exploration shows how these parents’ concerns are hooked into the institutional work of assessment for service discharge conducted by the Community Care Access Centre (CCAC) care coordinators. The analysis shows how the institutional category of ‘independence’ coordinates the service discharge work of the CCAC care coordinators with that of the nursing work of community nurses at school. The activation of the category of ‘independence’ by the nurses mediates their work, orienting their focus away from providing direct nursing care, and towards transferring primary care to children with diabetes. Children doing diabetes self-care work at school is then written up in nursing texts to stand in for children’s ability to manage diabetes ‘independently’. The textual production of ‘independence’ enables the next institutional course of action, that is, the discharge of children from nursing services at school. In this process, children with diabetes are drawn into doing the discharge work that ultimately serves the cost-containment interests of the institution. This institutional process also functions to obscure important actualities: It obscures how children’s ‘independence’ is co-created on a daily basis with their parents and relies on their parents’ work, and it discounts the significance of children with diabetes coming to their own embodied and emotional readiness for diabetes self-care.